Botryosphaeria sinensia sp nov., a new species from China - Zhou, Yupei; Dou, Zhipeng; He, Wei; Zhang, Xiaodong; Zhang, Ying (Phytotaxa, 2016)
A new Botryosphaeria species (B. sinensia) is described and illustrated from China. It is characterized by erumpent, botryose clustered ascostromata, ostiolate ascomata, bitunicate, 8-spored and clavate asci, filiform, rarely branched pseudoparaphyses, hyaline, 1-celled, fusiform ascospores, and a Fusicoccum asexual morph. The hyaline old and discharged conidia with 1–2 septa, broader spermatia formed in the culture and smaller ascostroma readily distinguished it from B. dothidea and other species in Botryosphaeria. The intergenic spacer (ITS)  and translation elongation factor 1-alpha (EF1) DNA sequence analysis results also support its separation from other Botryosphaeria species. Its relationships with other species of Botryosphaeria are also discussed based on morphology and DNA sequence comparisons.